Studi Literatur : Hubungan Pola Makan Dengan Kejadian Gastritis - Mevi Lilipory (MOLUCCAS HEALTH JOURNAL, 2021)
Gastritis is an acute, chronic diffuse or local inflammation of the gastric mucosa, with characteristics of anorexia, feeling full in the stomach (begah), discomfort in the epigastric, nausea, and vomiting. Based on data from the Word Health Organization (WHO, 2017), the incidence of gastritis in the world is about 1.8-2.1 million of the population each year, in the United Kingdom (22%), China (31%), Japan (14.5), Canada (35%), and France (29.5). In Southeast Asia about 586,635 of the population each year. Percentage of the incidence of gastritis in Indonesia  40.8% (WHO 2017). The incidence rate of gastritis in Indonesia is quite high with a prevalence of 274,396 cases. This research aims to find out the study of literature. relationship of diet with the incidence of gastritis. This type of research is descriptive using the Systematic Reviewmethod. The sample in the study totaled 4 national research journals related to the study title. The source of the database used is Google Scholar with reference to inclusion and exclusion criteria. Based article that have been analyzed, there is a neggine relationship between diet and stress with the incidence of gastritis.. It is recommended to people with gastritis to be able to control their diet, both time, type and portion of food so as not to trigger the occurrence of gastritis. Keywords: Gastritis, Diet